Comparison of Individual Air-Side Row-By-Row Heat Transfer Coefficient Correlations on Four-Row Finned-Tube Heat Exchangers. Issue 11 (4th July 2023) - Marcinkowski, Mateusz; Taler, Dawid; Taler, Jan; Węglarz, Katarzyna
Abstract: Each row of the heat exchanger (HEX) has different hydraulic-thermal characteristics. When the air velocity upstream of the HEX is lower than approximately 3 m/s, the exchanged heat flow rates at the first rows of tubes are higher than the average value for the entire HEX. The article presents the determination of the individual correlations for the air-side Nusselt numbers on each row of tubes for a 4-row finned HEX with continuous flat fins and round tubes in a staggered tube layout. The method was built based on computational fluid dynamics modeling. Mass average temperatures for each row were simulated for over a dozen different airflow velocities, from 2.5 m/s to 10 m/s. The obtained individual correlations for the air-side Nusselt number will enable selecting the optimum number of tube rows for a given heat output of the HEX. The investment costs of the HEX can be reduced by decreasing the tube row number. Moreover, the operating costs of the HEX can also be lowered, as the air pressure losses on the HEX will be lower, which in turn enables the reduction of the air fan power.